2021
DOI: 10.1523/jneurosci.0226-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

An Early Cortical Progenitor-Specific Mechanism Regulates Thalamocortical Innervation

Abstract: The cortical subplate is critical in regulating the entry of thalamocortical sensory afferents into the cortex. These afferents reach the subplate at embryonic day (E)15.5 in the mouse, but "wait" for several days, entering the cortical plate postnatally. We report that when transcription factor LHX2 is lost in E11.5 cortical progenitors, which give rise to subplate neurons, thalamocortical afferents display premature, exuberant ingrowth into the E15.5 cortex. Embryonic mutant subplate neurons are correctly po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…GSEA revealed that the biological processes associated with synaptic transmission, sensory perception, and protein localization to cilium were enriched in Lhx2 flox/ flox ovaries. In the brain, Lhx2 is involved in the development and patterning of the neurons involved in sensory perception [51,52]. In hypothalamic tanycytes, Lhx2 regulates the numbers of motile cilia by controlling the expression of FoxJ1 [53].…”
Section: Discussionmentioning
confidence: 99%
“…GSEA revealed that the biological processes associated with synaptic transmission, sensory perception, and protein localization to cilium were enriched in Lhx2 flox/ flox ovaries. In the brain, Lhx2 is involved in the development and patterning of the neurons involved in sensory perception [51,52]. In hypothalamic tanycytes, Lhx2 regulates the numbers of motile cilia by controlling the expression of FoxJ1 [53].…”
Section: Discussionmentioning
confidence: 99%
“…These findings also offer novel insights into how LHX2 adapts its roles at different stages of neurogenesis. Previous studies identified an early cortical progenitor-specific role of LHX2 that regulates the electrophysiological properties of the firstborn cells of the cortex, the subplate (27).…”
Section: Discussionmentioning
confidence: 99%
“…In utero electroporation was performed at E15.5 as previously described ( 27 ). Embryos were injected with plasmid DNA solution dissolved in nuclease-free water with 0.1% fast green with plasmid DNA into the lateral ventricle through the uterine wall using a fine glass microcapillary (Sutter capillaries #B100-75-10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers for genotyping were (expected band sizes): In utero, electroporation was performed as previously described (71). Embryos were injected with 1-2 μL of plasmid DNA solution dissolved in nuclease-free water with 0.1% fast green with plasmid DNA into the lateral ventricle through the uterine wall using a fine glass microcapillary (Sutter capillaries #B100-75-10).…”
Section: Micementioning
confidence: 99%